Optimizing outcomes in acute pancreatitis: the impact of of heparin therapy duration on mortality in a multi-center retrospective study - Linlin Fu; Hanyang Li; Qian Ni; Qiaoling Zhu; Baoyan Wang (BMC Gastroenterology)
Abstract Objective Acute pancreatitis is a critical condition in the intensive care unit (ICU), often complicated by systemic issues, which may benefit from heparin therapy due to its anti-inflammatory and anticoagulant properties. However, the optimal duration of heparin therapy remained unclear. This retrospective study aimed to evaluate the association between heparin therapy duration and mortality outcomes in patients diagnosed with acute pancreatitis. Method This retrospective study utilized data from the Medical Information Mart for Intensive Care (MIMIC-IV) and eICU Collaborative Research Database (eICU-CRD), including 1705 patients diagnosed with acute pancreatitis between 2008 and 2019. Restricted cubic splines (RCS) were employed to analyze the non-linear relationship between heparin therapy duration and 30-day and 90-day mortality. Patients were categorized into four groups based on quartiles: < 4 days, 4–7 days, 8–14 days, and > 14 days, using characteristics identified in the RCS curves, with 4–7 days as the reference. Cox multivariate regression and Kaplan-Meier analysis assessed the association between these groups and mortality, with 30-day mortality as the primary outcome and 90-day mortality as the secondary outcome. Result The relationship between heparin therapy duration and mortality at 30 and 90 days in patients with acute pancreatitis exhibited a J-shaped curve, with the lowest mortality observed around 7 days for both 30-day and 90-day mortality. Heparin therapy durations less than 4 days were significantly associated with higher 30-day mortality (HR: 2.57, 95% CI: 1.53–4.30) and increased 90-day mortality (HR: 1.57, 95% CI: 1.07–2.32), with mortality stabilizing beyond 7 days of therapy. Subgroup analysis stratified by severity consistently supported these findings. Conclusion In critically ill patients with acute pancreatitis, heparin therapy lasting less than 4 days was associated with increased 30-day and 90-day mortality, whereas the lowest mortality was observed among patients receiving heparin therapy for approximately 7 days.